1993
DOI: 10.1007/bf00303574
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa extradural hematomas in children: report of nine cases

Abstract: Extradural post-traumatic posterior fossa hematoma is a rare condition estimated to complicate about 0.13% of all craniocerebral injuries, and represents 5.8% of the entire group of extradural hematomas in our records. Nine cases of posterior fossa extradural hematomas are presented. The clinical picture was dominated by headache, vomiting, and gait ataxia. An occipital fracture was seen in 77.7% of the patients. In all cases, the diagnosis was made by computed tomography. The postoperative evolution was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
24
2
3
Order By: Relevance
“…Gupta et al [1], in their series of PFEDH in 19 children, reported 1 case of severe disability and 2 of moderate disability. There was 1 mortality and 1 moderate disability each in the report published by Berker et al [9 ]in their series of 16 children with PFEDH. Ciurea et al [9] reported 100% good outcomes in 9 cases of PFEDH, all managed surgically.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Gupta et al [1], in their series of PFEDH in 19 children, reported 1 case of severe disability and 2 of moderate disability. There was 1 mortality and 1 moderate disability each in the report published by Berker et al [9 ]in their series of 16 children with PFEDH. Ciurea et al [9] reported 100% good outcomes in 9 cases of PFEDH, all managed surgically.…”
Section: Discussionmentioning
confidence: 93%
“…There was 1 mortality and 1 moderate disability each in the report published by Berker et al [9 ]in their series of 16 children with PFEDH. Ciurea et al [9] reported 100% good outcomes in 9 cases of PFEDH, all managed surgically. Sencer et al [2 ]also reported 100% good outcomes in their study which included 40 cases.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations